A Development of Student Leadership Characteristic Practice Model at Normal Universities in Hebei Province, China - Yang, Yanan; Mhunpiew, Nathara (Scholar: Human Sciences, 2019)
Student leadership development provides students with opportunities to demonstrate and cultivate their leadership characteristics. In this research, the main purpose was to create a model for the development of student leadership characteristic practice at Normal Universities in Hebei Province of China. It applied both qualitative and quantitative methods. The researcher applied the content analysis about desirable student leadership characteristics in higher education. Skills, knowledge and attitude were crucial components of student leadership development, and the accomplished results of content analysis were validated by twenty-one experts. The researcher utilized survey questionnaires for data collection of 377 students, 243 teachers and 37 top-level administrators. The results of questionnaires, combined with interview data collection of 52 market employers of internship together as a reference revealed the areas that need urgent improvements. Student leadership theories and initial findings of first and second objective derived a preliminary model, after the experts’ validation and discussion; the researcher modified the nascent model until it became the final model. In the following step, the period of implementation included three months, which comprised student leadership conferences, local community service outreach, empowering leaders’ camp, co-curricular activities, and evaluation and feedback of student leadership characteristic practice, these called intervention program was developed based on the model. The results of differences between pre-test and post-test, which contained a total of 50 participants, proved that the model was undoubtedly effective with long-term significance. Eventually, the final model and the leadership training offered a potential programmatic option to help develop students as outstanding leaders.